KINERJA PUSKESMAS DONGGALA PADA PENGUNJUNG RAWAT JALAN DI PUSKESMAS DONGGALA KECAMATAN BANAWA KABUPATEN DONGGALA - Meylinda, Susana (Katalogis, 2015)
This study aims at determiniting the performance of Donggala PHC toward Outpatient Visitors at the PHC of subdistrict Banawa of District Donggala. The type of this research used is a descriptive research. And method used inthis research is a qualitative method. There are eight respondents in this research,consisting of: Head of Donggala PHC, Head of Administration, Head of Donggala BPJS Center, chasier section, elderly poly, drugs section, and two outpatient Visitor who are visiting the Donggala PHC. The results show that the performance of Donggala PHC is not satisfaying due to the quality of outpatient visitors services especially on outpatient visitors particulary general patients, which their fee rate charge is not in accordance to regional regulations applied. Then for the National Health Insurance Card holder who have not fully understood their rights, whether it is BPJS or Askes, this is due to the lack of socialization of regional BPJS center to recidents who hold the National Health Insurance Card.